1981
DOI: 10.1029/jb086ib05p04009
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic effects of maghemitization of oceanic crust

Abstract: Both theoretical considerations and available experimental results indicate that magnetic effects of maghemitization are strongly dependent on the grain size of the originally unoxidized titanomagnetite. Maghemitization of single‐domain titanomagnetite results in a decrease in coercivity, an increase in susceptibility, and a large decrease in Q ratio. Maghemitization of multidomain titanomagnetite results in an increase in coercivity, a decrease in susceptibility, and no large changes in Q ratio. Single‐domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 58 publications
1
37
0
Order By: Relevance
“…However, Prevot et al (1981) and Smith (1983) found an increase of the susceptibility for SD grains while a decrease was found for multidomain (MD) grains. The Koenigsberger ratio (Q) is related to the intensity of the NRM and to the susceptibility (K).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Prevot et al (1981) and Smith (1983) found an increase of the susceptibility for SD grains while a decrease was found for multidomain (MD) grains. The Koenigsberger ratio (Q) is related to the intensity of the NRM and to the susceptibility (K).…”
Section: Discussionmentioning
confidence: 99%
“…It seems well accepted that during maghemitization, in SD grains, Q decreases because the intensity of the remanence decreases more rapidly than the susceptibility. In MD grains, the measured Q value suggests that this parameter remains more or less constant during low temperature oxidation (Ade-Hall et al, 1976;Marshall, 1978;Prevot et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…after basalt emplacement. Other investigations on very young ocean-ridge basalts (Prévot et al, 1981;Kent and Gee, 1994) indicate an even shorter time constant by an order of magnitude for the maghemitization process.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of the laboratory Königsberger ratio (Q L ) and the viscosity index (VI), as described by e.g. Prévot et al (1981), were made for specimens from all core samples. These, together with other rock magnetic parameters measured for the samples used in this study are also given in Table 1.…”
Section: Samples and Experimental Methodologymentioning
confidence: 99%